2010
DOI: 10.3109/03639040903099751
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive liposomes as ocular delivery system: physical, microbiological, and in vivo assessment

Abstract: The results obtained pointed out that liposome coating process resulted in entrapment efficiency reduction and higher chitosan concentration, and molecular weight showed a more pronounced effect. No morphological differences between coated and uncoated liposomes were observed. Diffusion was the drug release mechanism from chitosomes. Concerning rheological behavior, pseudoplastic flow was characteristic to the prepared chitosomal dispersions. In addition, chitosan coating improved the ocular permeation of cipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 38 publications
2
32
0
1
Order By: Relevance
“…Dispersing liposomes in a viscous gel has been used either to reduce the rapid leakage of the encapsulated drug from liposomes (Meisnera & Mezeib, 1995) or to minimize the burst release effect observed with liposomes (Mehanna et al, 2009(Mehanna et al, , 2010. This approach may be extrapolated to improve the physical stability of ocular niosomes.…”
Section: Limitations and Future Directionmentioning
confidence: 99%
“…Dispersing liposomes in a viscous gel has been used either to reduce the rapid leakage of the encapsulated drug from liposomes (Meisnera & Mezeib, 1995) or to minimize the burst release effect observed with liposomes (Mehanna et al, 2009(Mehanna et al, , 2010. This approach may be extrapolated to improve the physical stability of ocular niosomes.…”
Section: Limitations and Future Directionmentioning
confidence: 99%
“…The rapid development of nano-technology of pharmaceutics brings new hope to resolve the difficulties in the ocular delivery. Such technologies include liposomes (Alsarra et al, 2008;Shehata et al, 2008;Pukanud et al, 2009;Mehanna et al, 2010), polymer nanoparticles (Oyarzun-Ampuero et al, 2009), lipid nanoparticles (Gokce et al, 2008), microemulsions (Chan et al, 2007), etc. Such formulations are suitable to be applied to a topical instillation for treatment of local ophthalmic diseases, and meanwhile the systematic adverse effects and clinical inconvenience during the treatment can be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan, a biodegradable and nontoxic mucoadhesive substance, has been used to coat liposomes. Mehanna et al (2010) showed that coating liposomes with high molecular weight chitosan inhibits their aggregation, increases the viscosity and hence the corneal residence time. The chitosan coating slowed the rate of drug release and provided 1.74-fold higher corneal permeation due to absorption enhancing nature of chitosan.…”
Section: Stability and Corneal Residence Timementioning
confidence: 99%